Twelve-month follow-up of a controlled trial of a brief behavioural intervention to reduce psychological distress in young adolescent Syrian refugees - Richard A. Bryant; Rand Habashneh; Maha Ghatasheh; Aiysha Malik; Ibrahim Said Aqel; Katie S. Dawson; Sarah Watts; Mark J. D. Jordans; Felicity L. Brown; Mark van Ommeren; Aemal Akhtar (Epidemiology and Psychiatric Sciences)
Abstract Aims The majority of studies of mental health interventions for young adolescents have only evaluated short-term benefits. This study evaluated the longer-term effectiveness of a non-specialist delivered group-based intervention (Early Adolescent Skills for Emotions; EASE) to improve young adolescents’ mental health.